2015
DOI: 10.1002/ejoc.201500227
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Free Synthesis of 4H‐Pyrido[1,2‐a]pyrimidin‐4‐ones Catalyzed by BiCl3: A Green Route to a Privileged Backbone

Abstract: An extensive array of 4H‐pyrido[1,2‐a]pyrimidin‐4‐ones have been synthesized from commercially available 2‐aminopyridines and β‐oxo esters with excellent yields under solvent‐free conditions. The reaction, catalyzed by cheap and nontoxic BiCl3, proceeds with short reaction times under mild conditions and normal atmosphere. Only water and alcohol are formed as co‐products in this green reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Copper then catalysed both the aerobic oxidation of tricarbonyls 45 to enone 47 as well as the subsequent intramolecular amide formation to afford 4 H ‐pyrido[1,2‐ a ]pyrimidin‐4‐ones 48 in moderate to good yield. A related study by Jaenicke et al showed that BiCl 3 was also an effective catalyst for the synthesis of pyrido‐pyrmidinones via an ATC process …”
Section: Auto‐tandem Catalysis Approaches To Heterocyclesmentioning
confidence: 99%
“…Copper then catalysed both the aerobic oxidation of tricarbonyls 45 to enone 47 as well as the subsequent intramolecular amide formation to afford 4 H ‐pyrido[1,2‐ a ]pyrimidin‐4‐ones 48 in moderate to good yield. A related study by Jaenicke et al showed that BiCl 3 was also an effective catalyst for the synthesis of pyrido‐pyrmidinones via an ATC process …”
Section: Auto‐tandem Catalysis Approaches To Heterocyclesmentioning
confidence: 99%
“…In order to arrive at suitable reaction conditions, initial optimization studies were carried out employing ethyl acetoacetate ( 1a ) and 2‐aminopyridine ( 2a ) as model substrates (Table ). Instead of BiCl 3 as catalyst for the synthesis of 4 H ‐pyrido[1,2‐ a ]pyrimidin‐4‐ones as reported by Jaenicke, we envisaged that I 2 can act as mild Lewis acid and can be employed for the coupling of 1a and 2a . When the reaction was performed with I 2 in methanol under reflux, we observed the formation of 2 H ‐pyrido[1,2‐ a ]pyrimidin‐2‐one instead of its regioisomer (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…The major limitation for the synthesis of this scaffold can be ascribed to the relative lack of synthetic flexibility for their construction. Jaenicke et al carried out the synthesis of 4 H ‐pyrido[1,2‐ a ]pyrimidin‐4‐ones from readily available 2‐aminopyridine and β‐oxo esters, but there were no reports on the synthesis of its regioisomer employing the same starting materials. Consequently, we envisioned to utilize mild, environmentally benign, non‐hygroscopic elemental sulfur as catalyst for the construction of 2 H ‐pyrido[1,2‐ a ]pyrimidin‐2‐ones from 2‐aminopyridines and β‐oxo esters by replacing the existing strategies which employs activated Baylis–Hillman adducts, microwave assistance, and added reagents.…”
Section: Introductionmentioning
confidence: 99%
“…It is a key constituent of numerous natural products possessing wide range of therapeutic properties including antitumor, anti-influenza, oxidative burst inhibition, lipid droplet synthesis inhibition, and anti-obesity properties12345678910. Recent studies have revealed that the molecules bearing pyrido-pyrimidinones are in different phases of drug development to treat cancer, hypertension, neurological disorders, etc111213141516. Some of them have been recognized as aldose reductase inhibitors, efflux pump inhibitors, and hepatitis C virus NS3 protease inhibitors.…”
mentioning
confidence: 99%
“…Bicyclic pyrimidones have also been synthesized by using β -oxo esters and 2-amnionpyrimidines in the presence of BiCl 3 catalyst (Fig. 3, Case C)11. The use of alkyne Michael addition helps in shifting the position of carbonyl group in pyrimidones19.…”
mentioning
confidence: 99%